(untitled) (Nigerian Journal of Technology, 2017)
We wish all our contributors, readers and reviewers a Happy New Year. We ended 2017 on a grand note after publishing over 120 articles in one year. We owe the greatest gratitude to the doggedness of our reviewers in all fields of technology. Getting an article on the journal is a tasking job, from submission, through review, decisions, re-reviews, etc as contained in our flowchart located at: www.nijotech.com. We start 2018 on a sound footing with a brand new issue. This issue, as usual, is packed with new ideas and innovations reported from several institutions. This time around, we have more contributions from outside Nigeria than ever before, an indication that our rankings, visibility and citations are improving. We cannot wish for less. NIJOTECH joined African Journal Online (AJOL) in 2012 and ever since, it has been rosy. We obtain all our Digital Object Identifiers (DOIs) from AJOL. They host all our issues on their website for proper dissemination of our contents at no additional cost. In 2017, they introduced a new citation indexing format in which they track all access to our websites. In this new issue, we are pleased to publish this unique statistics we obtained from AJOL as they track our article downloads, citations and abstract views all over the world. Several other information and details were made available to the editorial office from AJOL but for brevity, we will show only one graph. As can be seen in Figure 1, there were 7,688 abstract views and 117,581 article downloads between January and September 2017. As more articles get uploaded, these statistics are bound to improve, an evidence that we are heading to where we should be, a place where publications in Engineering and Technology of Sub-Saharan Africa and other tropical regions of the world is hosted